Financial frictions, investment and Tobin's q - Guido Lorenzoni; Karl Walentin (Sveriges Riksbank, 2007)
We develop a model of investment with financial constraints and use it to investigate the relation between investment and Tobin's q. Afirm is financed partly by insiders, who control its assets, and partly by outside investors. When their wealth is scarce, insiders earn a rate of return higher than the market rate of return, i.e., they receive a quasi rent on invested capital. This rent is priced into the value of the firm, so Tobin's q is driven by two forces: changes in the value of invested capital, and changes in the valu of the insiders' future rents per unit of capital. This weakens the correlation between q and investment, relative to the frictionless benchmark. We present a calibrated version of the model, which, due to this effect, generates realistic correlations between investment, q, and cash flow.
Keywords: E22; E30; E44; G30; 330; financial constraints; investment; Tobin's q; limited enforcement; Unternehmensfinanzierung; Investition; Kapitaleinkommen; Tobin's Q; Cash Flow